Advancing lean management: The missing quantitative approach - Antony Pearce; Dirk Pons (Operations Research Perspectives, 2019)
For 25 years, the methodologies employed to study lean management have gone relatively unchallenged. This paper reviews the development of the lean body of knowledge and reveals that the vast majority of research, being qualitative, relied heavily on researcher subjectivity. Quantitative analyses are needed to verify and strengthen existing literature and especially confirm the critical factors for lean success. Various theories requiring validation were identified and studies that incorporate Structural Equation Modelling were proposed. Such studies would advance industry practice, giving the tangible statistical evidence needed for educating practitioners. Practitioners are encouraged to consider the empirical basis of lean publications.
Keywords: 330; Lean; Management; Review; Research; Quantitative; Structural equation modelling